2021
DOI: 10.1038/s41598-021-91068-8
|View full text |Cite
|
Sign up to set email alerts
|

Accelerated mapping of electronic density of states patterns of metallic nanoparticles via machine-learning

Abstract: Within first-principles density functional theory (DFT) frameworks, it is challenging to predict the electronic structures of nanoparticles (NPs) accurately but fast. Herein, a machine-learning architecture is proposed to rapidly but reasonably predict electronic density of states (DOS) patterns of metallic NPs via a combination of principal component analysis (PCA) and the crystal graph convolutional neural network (CGCNN). With the PCA, a mathematically high-dimensional DOS image can be converted to a low-di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 56 publications
1
15
0
Order By: Relevance
“…With regards to model design, we note that there have been significant recent advances in graph neural network designs for materials chemistry applications. These approaches can be incorporated in our framework with only minor changes to our overall workflow. Additional avenues for improvement can also include better output representations for the DOS, such as using a principal component basis ,, or using autoencoders, , which would help by reducing the output dimensions, as long as the reconstruction errors are sufficiently low. Alternatively, coupling the ML predictions to a physical model such as a tight-binding model or a lower level of DFT theory in a Δ-ML approach could be used to improve accuracy and reduce data requirements.…”
Section: Discussionmentioning
confidence: 99%
“…With regards to model design, we note that there have been significant recent advances in graph neural network designs for materials chemistry applications. These approaches can be incorporated in our framework with only minor changes to our overall workflow. Additional avenues for improvement can also include better output representations for the DOS, such as using a principal component basis ,, or using autoencoders, , which would help by reducing the output dimensions, as long as the reconstruction errors are sufficiently low. Alternatively, coupling the ML predictions to a physical model such as a tight-binding model or a lower level of DFT theory in a Δ-ML approach could be used to improve accuracy and reduce data requirements.…”
Section: Discussionmentioning
confidence: 99%
“…Generally, they are in the ratio of 7 : 3. 65 There are many kinds of predictable machine learning models being selected, but we have to match the selection by weighing between its predictive accuracy, computational cost and feasibility. 66,67 The predictive power is usually affected by the amount of data in the test set, the choice of kernel function and the definition of loss function in the data set.…”
Section: Algorithmmentioning
confidence: 99%
“…Emphasizing the importance of physically meaningful descriptors, various studies have shown excellent mapping of bulk band gaps onto compositional representations for the materials. Single-value scalars such as band gap, ionization energy, and electron affinity are commonly used descriptors, and even the densities of states have been used as a complex input feature for mapping the relationship between materials and their electronic structure. …”
Section: Design Metrics Of Materials: Bulk To Nanomaterialsmentioning
confidence: 99%
“…Single-value scalars such as band gap, ionization energy, and electron affinity are commonly used descriptors, 101 and even the densities of states have been used as a complex input feature for mapping the relationship between materials and their electronic structure. 102 104 …”
Section: Design Metrics Of Materials: Bulk To Nanomaterialsmentioning
confidence: 99%